The Scientific Role of The Scholars of The Jazira Region in The Levant in The Seventh Century AH / Thirteenth Century AD - Hassan, Qadir Muhammad; Abdul Rahman, Roshan Ramadan (Zanco Journal of Human Sciences, 2024)
This research is dedicated to shedding light on the scientific activities of the scholars of the Jazira region in the field of transmission sciences in the Levant, during the seventh century AH / thirteenth century AD, such as the sciences of the Qur’an, the science of readings, the science of interpretation, the science of hadith and jurisprudence, and the science of Sufism, which is intended by (Communicative sciences) in this research are the religious sciences that are directly related to the sciences of the Qur’an and the noble hadiths of the Prophet. It contains many island scholars in the Levant, as well as a study of the science of jurisprudence and its origins and the role of the island’s scholars in this field in the Levant.